Influence of physical strain at high altitude on the quality of cardiopulmonary resuscitation - Alexander Egger; Maximilian Niederer; Katharina Tscherny; Josef Burger; Verena Fuhrmann; Calvin Kienbacher; Dominik Roth; Wolfgang Schreiber; Harald Herkner (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine, 2020)
Abstract Background High quality cardiopulmonary resuscitation is a key factor in survival with good overall quality of life after out-of-hospital cardiac arrest. Current evidence is predominantly based on studies conducted at low altitude, and do not take into account the special circumstances of alpine rescue missions. We therefore aimed to investigate the influence of physical strain at high altitude on the quality of cardiopulmonary resuscitation. Methods Alpine field study. Twenty experienced mountaineers of the Austrian Mountain Rescue Service trained in Basic Life Support (BLS) performed BLS on a manikin in groups of two for 16 min. The scenario was executed at baseline altitude and immediately after a quick ascent over an altitude difference of 1200 m at 3454 m above sea level. The sequence of scenarios was randomised for a cross over analysis. Quality of CPR and exhaustion of participants (vital signs, Borg-Scale, Nine hole peg test) were measured and compared between high altitude and baseline using random-effects linear regression models. Results The primary outcome of chest compression depth significantly decreased at high altitude compared to baseline by 1 cm (95% CI 0.5 to 1.3 cm, p < 0.01). There was a significant reduction in the proportion of chest compressions in the target depth (at least 5 cm pressure depth) by 55% (95% CI 29 to 82%, p < 0.01) and in the duration of the release phase by 75 ms (95% CI 48 to 101 ms, p < 0.01). No significant difference was found regarding hands-off times, compression frequency or exhaustion. Conclusion Physical strain during a realistic alpine rescue mission scenario at high altitude led to a significant reduction in quality of resuscitation. Resuscitation guidelines developed at sea level are not directly applicable in the mountain terrain.